Youth Engagement-Engaging for Change: Changing for Engagement - Yoshitaka Iwasaki (The University of Alabama, 2022)
This paper documents the incentives for, processes of, and outcomes from our multi-year community-based research project on youth engagement. In line with the theme of the 15th Annual Conference of the Engagement Scholarship Consortium (ESC)-Engaging for Change: Changing for Engagement-this paper illustrates our project in terms of the conference's three sub-themes: (1) Why engage?, (2) How do we engage?, and (3) What impacts are we having? Contextualized within these sub-themes, the paper describes opportunities and challenges of youth engagement from youth and professional perspectives by highlighting insights of our youth leaders and community partners, along with some reflective remarks by our university researchers. The paper provides tangible descriptions and illustrations for the significance of "strategic engagement" (Speer & Christens, 2013) by focusing on the use of "strategic youth and partner engagement." Importantly, this strategic engagement centerpieces the voices and talents of our youth leaders, supported by our community agency partners, along with a background role of university researchers.